Realizing the therapeutic potential of rapid knockdown of transthyretin via RNA interference in transthyretin amyloidosis - Martha Grogan; Farooq H. Sheikh; Brett W. Sperry; Marianne T. Sweetser; Kelley Capocelli; Steven Roblin; Ronald Witteles (Molecular Therapy: Nucleic Acids)
RNA interference (RNAi) is a natural biological mechanism that regulates gene expression by degrading a specific target messenger RNA, resulting in reduced production of the target protein. RNAi therapeutics can silence the production of a disease-causing protein in a specific organ or cell type and have the advantage of having a long duration of effect due to their inherently stable duplex structure and chemical modifications. Following the development of RNAi-based platform technologies, a growing number of RNAi therapeutics have now been approved across a range of diseases. Transthyretin amyloidosis (ATTR) is a progressive, debilitating, and fatal disease caused by ongoing accumulation of toxic transthyretin (TTR) amyloid deposits in multiple organs and tissues. This review describes the clinical development of patisiran and vutrisiran, which target the hepatic production of TTR for the treatment of ATTR amyloidosis. Findings from clinical studies show that rapid knockdown of TTR by RNAi therapeutics initiates a cascade of effects that ultimately leads to benefits across multiple clinical, quality of life, imaging, and biomarker disease measures of ATTR amyloidosis disease progression.